2016
DOI: 10.1039/c6dt02672a
|View full text |Cite
|
Sign up to set email alerts
|

A structurally flexible triazolate-based metal–organic framework featuring coordinatively unsaturated copper(i) sites

Abstract: The novel metal-organic framework CFA-8 (Coordination Framework Augsburg University-8), [Cu2(tqpt)], containing the organic linker H2-tqpt {H2-tqpt = 6,6,14,14-tetramethyl-6,14-dihydroquinoxalino[2,3-b]phenazinebis-triazole}, has been synthesized. Reaction of H2-tqpt and anhydrous CuCl2 in N,N-dimethylacetamide (DMA) yields CFA-8 as orange crystals with lenticular shape. This framework shows a reversible breathing effect and is robust upon solvent removal. It has been characterized by single-crystal and powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…17 Recent research has shown that MOFs can reversibly adsorb relatively large quantities of carbon monoxide through reversible interaction with open metal centers at low temperatures. 18 The enthalpies of adsorption for CO were in the range 19-53 kJ mol -1 for temperatures in the range 77-318 K. [18][19][20] CO is known to coordinate with metals but there is currently only evidence for weak interactions with metals in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recent research has shown that MOFs can reversibly adsorb relatively large quantities of carbon monoxide through reversible interaction with open metal centers at low temperatures. 18 The enthalpies of adsorption for CO were in the range 19-53 kJ mol -1 for temperatures in the range 77-318 K. [18][19][20] CO is known to coordinate with metals but there is currently only evidence for weak interactions with metals in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…To discuss the relation between the catalytic performance and structure of the hybrid CoPcTs‐Zn 2 Al‐LDH, a series of controlled reactions have been performed (Table ). Addition of BHT (2, 6‐Di‐tertbutyl‐4‐methylphenol) quenched the reaction (entry 2), demonstrating that radical species was formed as the key intermediate for the reaction . Without NHPI, CoPcTs‐Zn 2 Al‐LDH could not activate ethylbenzene (entry 3), indicating that NHPI was necessary in the catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of BHT (2, 6-Di-tertbutyl-4-methylphenol) quenched the reaction (entry 2), demonstrating that radical species was formed as the key intermediate for the reaction. [40][41] Without NHPI, CoPcTs-Zn 2 Al-LDH could not activate ethylbenzene (entry 3), indicating that NHPI was necessary in the catalytic system. The results of the blank reaction showed that NHPI could accelerate the oxidation even without catalysts (entry 4).…”
Section: Controlled Experimentsmentioning
confidence: 99%
“…The middle ground between these two extremes is to employ semi-rigid ligands with a smaller degree of flexibility, which have also been successfully employed to afford porous networks. [24][25][26][27][28][29][30][31] Benzotriazole and its derivatives have been frequently employed in the construction of CPs and MOFs [32][33][34][35][36][37][38][39][40][41][42][43][44] as well as polynuclear coordination clusters (CCs). [45][46][47][48] Its multi-modal coordination ability, through the 1,2,3-triazole moiety, provides enormous versatility when combined with transition metal ions.…”
Section: Introductionmentioning
confidence: 99%